Phillips' science of dental materials - Anusavice, Kenneth J; Phillips, Ralph W (Saunders, 2003)
This thoroughly revised text covers the most current dental materials available. Among the features are hundreds of high-quality illustrations and clinical photos to aid in learning the step-by-step process of important procedures
Keywords: Dental materials; Tandheelkunde; Dental Materials